Stalagmite-inferred European westerly drift in the early Weichselian with centennial-scale variability in marine isotope stage 5a. (15th July 2022) - Chung, Yun-Chuan; Menviel, Laurie; Marchionne, Arianna; Mii, Horng-Sheng; Michel, Véronique; Valensi, Patricia; Jiang, Xiuyang; Simon, Patrick; Rossoni-Notter, Elena; Moussous, Abdelkader; Seppä, Heikki; Chien, Yu-Tang; et al.
Abstract: The Weichselian glaciation is characterized by significant ocean circulation variations starting from ∼115 thousand years ago (ka) and terminating at ∼11.5 ka. The early Weichselian (115–74 ka), especially marine isotope stage (MIS) 5a at 85–74 ka, provides a window for understanding the linkage between the European westerlies and Mediterranean climate. However, lack of highly-resolved paleoclimate records with absolute chronologies hampers our knowledge of decadal-to-centennial-scale climate changes and forcings in the circum-Mediterranean realm. Here, we present 230 Th-dated stalagmite-inferred hydroclimate records from Observatoire cave (43°44′ N, 7°25' E), Monaco, for the period between 88.7 ± 0.4 and 80.3 ± 0.1 ka, covering portions of MIS 5b and 5a. Agreement between Observatoire and circum-Mediterranean stalagmite records confirm large-scale warming over the Atlantic-Europe territory during the transition from MIS 5b to 5a. Subdecadally-resolved Observatoire δ 18 O and δ 13 C records express four multi-centennial arid intervals in southern Europe at 84–80 ka in the first-half of MIS 5a, suggesting centennial westerly drifts, a finding supported by a model simulation. Westerly changes and associated arid events can be attributed to slowdowns of the Atlantic meridional overturning circulation, North Atlantic Oscillation states, and solar activity. Highlights: Stalagmite δ 18 O and δ 13 C records from Monaco show precipitation changes in southern Europe from 89 to 80 ka at MIS 5b-5a. Multi-centennial arid events at 84-80 ka during MIS 5a could be linked to AMOC slowdowns, NAO states, and solar activity. Models suggest that centennial-scale AMOC slowdowns at MIS 5a could induce reduced precipitation over western Europe.